PENGGUNAAN LAGU DALAM PEMBELAJARAN BAHASA INGGRIS UNTUK SISWA SD; MENGAPA DAN BAGAIMANA - Nurhayati, Lusi (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This article will describe the advantages of song to support English language learning process and also review some methods to use songs in English classroom. Moreover, this article will explain the position of English language in Indonesia and the characteristic of children as foreign language learners. Children have unique characteristics that could be employed for the supporting factors and disadvantaging factors of foreign language learning process. They need to move, be able to concentrate for a short term, learning through experiences, less ability to control and plan their activities, not fear to do some mistakes or take risks, not really paying attention to their shelves or their actions, paying attention to the language purposes and possessing limited experiences in their lives. Songs are learning resources that have so many advantages, including linguistics resource, affective/psychological resource, and cognitive resource. Songs also can be used as a media to teach four major skills, which are speaking, reading and writing. Another language skill such as pronunciation, vocabulary and grammar can be learnt wit the use of songs as well. Songs can be good learning sources for English language class. It would be better if English language teachers in elementary schools realize the advantages of using songs in the learning process to improve the quality of English language learning process. Using textbooks is no longer sufficient. Teachers are demanded to be creative in creating class activities to stimulate children so that they become interested toward English language. Hence, their interests toward English language would be an essential foundation to achieve the more satisfied English language capability.